Myofibroblasts in hollow visceral myopathy: the origin of gastrointestinal fibrosis?. Issue 7 (July 1993) - Martin, J E; Benson, M; Swash, M; Salih, V; Gray, A
Abstract : A patient with hollow visceral myopathy is reported in whom light microscopical studies of the small and large intestine showed typical features of degeneration, thinning, and fibrous replacement of smooth muscle of the gastrointestinal tract. Electron microscopy showed a striking increase in collagen with minimal fibroblast proliferation. Smooth muscle fibres had a range of ultrastructural abnormalities including myofilament disarray, electron lucency of the cytoplasm, and proliferation of the endoplasmic reticulum. Some fibres seemed to have typical ultrastructural characteristics of myofibroblasts, and others to be transition forms between typical smooth muscle cells and typical myofibroblasts. It seems likely that the fibrosis typical of this disorder has its origin in the transformation of smooth muscle fibres from a purely contractile to a myofibroblast collagen synthetic phenotype.